2007
DOI: 10.1016/j.diabet.2007.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal hypoglycaemias in type 1 diabetic patients: what can we learn with continuous glucose monitoring?

Abstract: NH were highly prevalent and often undetected. SMBG at bedtime, which detected hypoglycaemia had sensitivity almost equal to that of 3-hour and should be preferred because it is easier to perform. Somogyi phenomenon was not observed. CGMS is useful to reduce the risk of NH in 75% of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…Studies using this approach have generally found that the frequency and duration of hypoglycemia, especially nocturnal hypoglycemia, are greater than what was previously thought. 26,27 More reliable data are available from studies of severe hypoglycemia, which is defined as hypoglycemia associated with loss of consciousness or requiring external assistance. 14 Renal hypoglycemia (hypoglycemia associated with CKD without any other obvious cause) is known to occur spontaneously in nondiabetic individuals, with an incidence of 1% to 3%.…”
Section: Epidemiologymentioning
confidence: 99%
“…Studies using this approach have generally found that the frequency and duration of hypoglycemia, especially nocturnal hypoglycemia, are greater than what was previously thought. 26,27 More reliable data are available from studies of severe hypoglycemia, which is defined as hypoglycemia associated with loss of consciousness or requiring external assistance. 14 Renal hypoglycemia (hypoglycemia associated with CKD without any other obvious cause) is known to occur spontaneously in nondiabetic individuals, with an incidence of 1% to 3%.…”
Section: Epidemiologymentioning
confidence: 99%
“…Indeed, in their study, the CGMS underestimated BG in the low BG range, as determined using reference BG values, suggesting that asymptomatic hypoglycemic events detected by a CGMS may not have been true hypoglycemia. 12 Irrespective of whether CGMS overestimates or underestimates BG levels in the hypoglycemic range, the susceptibility of a CGMS to error in the low BG range, as well as the considerable variation in the definition and assessment of hypoglycemia, suggests that studies showing that CGMSs are useful for detecting hypoglycemia 2,7,[43][44][45][46][47][48] should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…2007 г., в котором приняли участие 88 человек с СД1, использующих НМГ. Авторы не выявили связи ночных гипогликемий с гипергликемией натощак (феноменом Сомоджи), однако прослеживалась связь ночных гипо-гликемий с низким уровнем глюкозы в последующее утро (OR=3,95, P=0,001) [23].…”
Section: последующие исследования феномена сомоджиunclassified